1991
DOI: 10.1016/s0022-5347(17)37958-2
|View full text |Cite
|
Sign up to set email alerts
|

Fibrinolytic Parameters in Spermatozoas and Seminal Plasma

Abstract: Urokinase-type (u-PA) and tissue-type plasminogen activator antigen (t-PA) as well as plasminogen activator-inhibitor activity were determined in seminal plasma and lysates of the respective spermatozoas in 67 ejaculate of males in infertile marriage without genito urinary pathology. U-PA was determined by a competition RIA, t-PA by an ELISA and PAI by a spectrophotometric assay. 15 patients showed normozoospermia, 11 azoospermia and 41 oligoasthenoteratozoospermia (OAT-syndrome). In lysates of spermatozoas, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
18
1

Year Published

1992
1992
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 12 publications
5
18
1
Order By: Relevance
“…Two types of PA proteins have been identified in mammals based on biochemical, immunological and functional properties: (1) t-PA, which is synthesized by a large number of tissues and plays a major role in regulating intravascular fibrinolysis, and (2) u-PA, which was first identified in human urine and later in various tissues; the latter is involved mainly in the degradation of extracellular matrix proteins associated with cell migration and tissue remodelling phenomena (Dano et al., 1985). The presence of different PAS as well as fibrinolytic inhibitors has been shown in seminal plasma and/or spermatozoa from man and animals (Smokovitis et al, 1987;Huarte et al, 1987;Maier et al, 1991).…”
Section: Discussionmentioning
confidence: 99%
“…Two types of PA proteins have been identified in mammals based on biochemical, immunological and functional properties: (1) t-PA, which is synthesized by a large number of tissues and plays a major role in regulating intravascular fibrinolysis, and (2) u-PA, which was first identified in human urine and later in various tissues; the latter is involved mainly in the degradation of extracellular matrix proteins associated with cell migration and tissue remodelling phenomena (Dano et al., 1985). The presence of different PAS as well as fibrinolytic inhibitors has been shown in seminal plasma and/or spermatozoa from man and animals (Smokovitis et al, 1987;Huarte et al, 1987;Maier et al, 1991).…”
Section: Discussionmentioning
confidence: 99%
“…Maier et al observed significantly higher t-PA concentrations in the spermatozoa of patients with oligoasthenoteratozoospermia (OAT syndrome) than in normozoospermic men (34). Moreover, t-PA concentrations in the ejaculate were also significantly higher compared to u-PA, and the t-PA and u-PA concentrations in the ejaculate were comparable between normozoospermic and oligozoospermic men (34).…”
Section: Male Study Populationmentioning
confidence: 98%
“…Very recently the presence of high tissue plasminogen activator antigen has been reported again by Maier et al (10) both in spermatozoa and in seminal plasma. Little is known about the role of tissue plasminogen activator activity.…”
Section: Discussionmentioning
confidence: 72%